Right Frontotemporal Cortex Mediates the Relationship between Cognitive Insight and Subjective Quality of Life in Patients with Schizophrenia - Pu, Shenghong; Nakagome, Kazuyuki; Itakura, Masashi; Ohtachi, Hiroaki; Iwata, Masaaki; Nagata, Izumi; Kaneko, Koichi (Frontiers in Psychiatry, 2018)
Although prior studies identified a relationship between cognitive insight and subjective quality of life (QOL) in patients with schizophrenia, the brain regions mediating this relationship remain unknown. Recent studies have shown that the ventrolateral prefrontal cortex (VLPFC) may be particularly important for cognitive insight in individuals with schizophrenia. Here, we examined whether fronto-temporal function mediates the relationship between cognitive insight and QOL in 64 participants, including 32 patients with schizophrenia and 32 healthy controls. Cognitive insight was measured using the Beck Cognitive Insight Scale, while participants’ subjective QOL was assessed using the Medical Outcomes Study 36-item Short-form Health Survey. Fronto-temporal function was evaluated during a verbal fluency task using 52-channel near-infrared spectroscopy. Consistent with previous findings, we found that fronto-temporal function was impaired in patients with schizophrenia. Interestingly, our data also revealed that the right VLPFC and the right anterior part of the temporal cortex significantly mediated the relationship between the self-reflectiveness subscale of the BCIS and subjective QOL. These findings suggest that cognitive insight, particularly self-reflectiveness, is associated with subjective QOL in patients with schizophrenia via right fronto-temporal function. The findings of the present study provide important insight into a QOL model of schizophrenia, which may guide the development of cost-effective interventions that target fronto-temporal function in patients with schizophrenia.